The dynamics of women's labour supply in developing countries - Sonia Bhalotra; Marcela Uma\~na-Aponte (Institute for the Study of Labor (IZA), 2010)
This paper investigates cyclicality in women's labour supply motivated by the hypothesis that it contributes to smoothing household consumption in environments characterized by income volatility. We use comparable individual data on about 1.1 million women in 63 developing and transition countries merged with country-level panel data on GDP during 1986-2006. The scope of these data is unprecedented in the small but growing literature on labour markets in developing countries. We find that the within-country relationship of women's employment and income is, on average, negative in Asia and Latin America but positive in Africa. We suggest that amongst reasons why African women behave differently are that the conventional family structure with income pooling is less the norm, there are fewer opportunities for paid employment, and aggregate income shocks are more closely tied to rainfall variation. The findings are robust to controls for country-specific trends and potentially correlated shocks. In Asia and Latin America, characteristics that strengthen counter-cyclical responses include low education, being married, being married to men with low education, low wealth, no landownings, rural residence and fertility. These findings suggest that insurance motives underpin the dynamics of women's work participation. Examination of cyclicality in the distribution of employment across types suggests that recessions in every region are associated with a rise in self-employment amongst women. In Asia and Latin America, there is a parallel rise in paid employment and a sharp drop in non-employment. In Africa, there is a decline in paid employment which overwhelms the rise in self-employment and this is how total employment comes to decline. The results have potentially important implications for understanding labour markets, fertility timing and child outcomes.
Keywords: J22; J13; 330; Insurance; women's labour supply; added worker effect; business cycles; dynamics; Africa; Asia; Latin America; Frauenerwerbstätigkeit; Arbeitsangebot; Konjunktur; Verdienstausfall; Haushaltseinkommen; Haushaltsökonomik; Vergleich; Entwicklungsländer; Afrika; Asien; Lateinamerika